Necromantica enteogena. Therapies and Psychoactive Virtues between Greece and Iran - Albrile, Ezio (Gerión. Revista de Historia Antigua, 2012)
The ancient world meets a variety of books of prescriptions extolling the therapeutic virtues of plants, herbs, stones and animal parts. Among them there is the so-called Letter of vultures, few scanty pages dedicated to the medical properties of a bird of ill repute.The text of the letter is based on some fundamental issues: there is an art medical, taught the Persian kings, that links the members of the vulture to illnesses; the divine virtue acting on the parts of the animal to treat a variety of ailments. Birds are also the subject of a famous comedy by Aristophanes, staged the first time at the Great Dionysia in the 414 BC. The plot is simple than mocking, and hidden psychoactive and entheogenic background in which a necromancer Socrates leads the souls in the afterlife. Socrates makes the rite close to a lake, that is located at the mysterious people of the Skiapodes, «feet that shade». Ethnography and the ancient religious history allow us to reconstruct the nature of this people in the light of Iranian Zoroastrian traditions.